Prediction of Fracture Evolution and Groundwater Inrush from Karst Collapse Pillars in Coal Seam Floors: A Micromechanics-Based Stress-Seepage-Damage Coupled Modeling Approach - Yinlong Lu; Bingzhen Wu; Mengqi He; Lianguo Wang; Dan Ma; Zhen Huang (Geofluids)
Karst collapse pillars (KCPs) frequently cause severe groundwater inrush disasters in coal mining above a confined aquifer. An accurate understanding of the damage and fracture evolution, permeability enhancement, and seepage changes in KCPs under the combined action of mining-induced stress and confined hydraulic pressure is of great significance for the early prediction and prevention of groundwater inrush from KCPs in coal seam floors. In this study, a micromechanics-based coupled stress-seepage-damage (SSD) modeling approach, in which the macroscopic mechanical and hydraulic properties of the rock are explicitly related to the microcrack kinetics, is proposed to simulate the fracture evolution and the associated groundwater flow in KCPs. An in situ high-precision microseismic monitoring technology is used to verify the micromechanical modeling results, which indicate that the numerical model successfully reproduces the damage and fracture evolution in a coal seam floor with a KCP during the mining process. The presented model also provides a visual representation of the complex process of KCP activation and groundwater inrush channel formation. A numerical study shows that the damage and activation of a KCP start from the edge of the KCP, gradually develop toward the interior of the KCP, and eventually connect with the damage fracture zone of the floor, forming a primary water-conducting channel in the KCP, causing the confined groundwater to flow into the working face. Groundwater inrush from a KCP is a gradual process instead of a mutation process. A reduction in the distance between the working face and a KCP and increases in the confined hydraulic pressure and the initial water-conducting height of the KCP can significantly increase the risk of groundwater inrush from the KCP.